PENGARUH LABEL HALAL DAN PENGETAHUAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK: RELIGIUSITAS SEBAGAI VARIABEL MODERASI - Febrianto, Diva; Utami, Datien Eriska (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to determine the effect of halal labeling and product knowledge on purchasing decisions with religiosity as a moderating variable for buying halal cosmetic products. Methods: This research uses quantitative methods. The population used in this study was residents of Sukoharjo who had bought cosmetic products. The sampling method used in this research is non-probability sampling with a purposive sampling technique. The analytical tool used is SmartPLS version 3.Results: Halal labeling has a positive and significant effect on purchasing decisions, product knowledge has a positive and significant effect on buying decisions, and religiousness has a positive and significant effect on purchasing decisions. Religiosity does moderate the relationship between halal labelling and purchasing decisions, but it does not moderate the relationship between product knowledge and purchasing decisions. This study explains how halal labeling and product knowledge affect purchasing decisions, and religiosity as a moderating variable strengthens consumers ' decisions in cosmetic purchasing. Keywords: Halal Label, Product Knowledge, Religiosity, Purchasing Decision